Place of articulation of anterior nasal versus oral stops in Croatian - Liker, Marko; Gibbon, Fiona E. (2014)
The purpose of this investigation is to analyse the place of articulation of anterior nasal versus oral stops in Croatian. Although there is agreement that placement for /n/ and /t d/ is in the anterior region, there is disagreement among different authors about the precise place of articulation for these sounds. Some authors view these targets as sharing identical placement while others view placement of /n/ as more posterior to /t d/. In this paper we use electropalatography (EPG) to investigate whether placement for these sounds is the same or different. The speech of six participants was recorded for the purposes of this study. The speech material consisted of 972 VCV sequences (V = /i a u/, C = /n t d/). Four EPG indices were analysed: the ACoG measure, the amount of contact at dental and alveolar articulatory zones (dentoalveolar articulation being inferred indirectly), incomplete EPG closures and the lateral contact measure. Coarticulatory effects of vowels on placementwere also measured. The results showed that /n t d/ generally shared the place of articulation in the dentoalveolar region, but also that relating quantitative physiological data to specific places of articulation should be done cautiously, taking into account variability in individual productions. The analyses also showed that /n/ had more incomplete EPG closures and a significantly lower amount of lateral contact when compared with /t/ and /d/. The nasal was more variable and showed less coarticulatory resistance in different vowel contexts than /t/ and /d/. The results of this study are discussed in terms of existing descriptions of Croatian consonant system and in light of cross-linguistic findings.
ENG